Isolation of Sango viruses from Israeli symptomatic cattle - Natalia Golender; Velizar Bumbarov; Avi Eldar; Lior Zamir; Boris Even Tov; Gabriel Kenigswald; Eitan Tiomkin (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
Sango Virus (SANV) is a member of the Simbu serogroup within the order Bunyavirales, family Peribunyaviridae, genus Orthobunyavirus. In the end of October, 2019, two SANV virus were identified and isolated from sera sampled from two symptomatic cows, which manifested fever, milk reduction and diarrhea. Two viruses were isolated in Vero cells. Full genome sequencing of these virus isolates was performed. Genetic and phylogenetic analyses of Israeli SANV strains showed their very close relationship. However, they have significant difference in all three genome segments with a sole known isolated Nigerian SANV Ib An 5077 strain.